The Influence of Regional Taxes, Regional Levies, General Allocation Funds and Special Allocation Funds on Capital Expenditures in Regency and City Regional Governments of South Sumatra Province in the Period 2012 - 2020 - Mat Ius; Keri Boru Hotang (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2024)
Purpose – The aim of this research is to examine the influence of regional taxes, regional levies, general allocation funds and special allocation funds on capital expenditure in district and city governments in South Sumatra province in the 2012-2020 period. Design/methodology/approach – The method used in this research uses a quantitative method by drawing samples using a purposive sampling technique, namely using samples with certain criteria, the samples used in this research are 11 districts and 2 cities in the district and provincial city governments South Sumatra in the 2012-2020 period. The data used is secondary data, namely data obtained in the form of annual APBD data reports and other supporting data in the public sector which is recorded at the Ministry of Finance, Directorate General of Financial Balance from the website https://djpk.kemenkeu.go.id/. The data analysis technique used to test the hypothesis is multiple regression analysis using Eviews9 software. Findings – Based on the results of the research, it was found that regional taxes have a positive and significant influence on capital expenditure, just as regional levies have a positive and significant influence on capital expenditure, as well as general allocation funds which have a positive and significant influence on capital expenditure, but special allocation funds have a negative and insignificant effect on capital expenditure. Research limitations/implications – This research can provide several suggestions for further research. Suggestions put forward by researchers include using other variables that are thought to influence capital expenditure or conducting research in other provinces.